Development and Validation of the Stroke Symptom Cluster Scale Among Korean Stroke Survivors: Mixed-Methods Design. Issue 6 (November 2021) - Song, Rhayun; Ahn, Sukhee; Jang, Taejeong; Oh, Jiwon; Sohn, Min Kyun
Abstract: Purpose: This study aimed to develop and validate the Stroke Symptom Cluster Scale for Korean Adults (SSCS-K) for stroke survivors. Design: An exploratory sequential study with a mixed-methods design was performed. Methods: In the development stage, a qualitative study with in-depth interviews was conducted with 27 stroke patients. The validation stage involved analyzing the psychometric properties from 288 stroke patients. Findings: The SSCS-K comprising 65 items in six dimensions (mobility, cognition, sensory, mood, communication, and swallowing difficulty) demonstrated acceptable internal consistency (Cronbach's α = .92–.94). Confirmatory factor analyses with a six-factor solution showed that it explained 62% of the variance in stroke symptoms. The concurrent validity was confirmed with the Stroke-Specific Quality of Life Scale ( r = .38–.83, p < .001). Conclusion: The SSCS-K has strong psychometric properties as a measure to assess clustered symptoms in stroke survivors during their long-term rehabilitation. Clinical Relevance: Rehabilitation nurses may consider the SSCS-K as a useful tool for assessing symptoms of stroke survivors.